An Efficient Gene Excision System in Maize - Wang, Ning; Arling, Maren; Hoerster, George; Ryan, Larisa; Wu, Emily; Lowe, Keith; Gordon-Kamm, William; Jones, Todd J.; Chilcoat, N. Doane; Anand, Ajith (Frontiers in Plant Science, 2020)
Use of the morphogenic genes Baby Boom (Bbm) and Wuschel2 (Wus2), along with new ternary constructs, has increased the genotype range and the type of explants that can be used for maize transformation. Further optimizing the expression pattern for Bbm/Wus2 has resulted in rapid maize transformation methods that are faster and applicable to a broader range of inbreds. However, expression of Bbm/Wus2 can compromise the quality of regenerated plants, leading to sterility. We reasoned excising morphogenic genes after transformation but before regeneration would increase production of fertile T0 plants. We developed a method that uses an inducible site-specific recombinase (Cre) to excise morphogenic genes. The use of developmentally regulated promoters, such as Ole, Glb1, End2, and Ltp2, to drive Cre enabled excision of morphogenic genes in early embryo development and produced excised events at a rate of 25–100%. A different strategy utilizing an excision-activated selectable marker produced excised events at a rate of 53–68%; however, the transformation frequency was lower (13–50%). The use of inducible heat shock promoters (e.g. Hsp17.7, Hsp26) to express Cre, along with improvements in tissue culture conditions and construct design, resulted in high frequencies of T0 transformation (29–69%), excision (50–97%), usable quality events (4–15%), and few escapes (non-transgenic; 14–17%) in three elite maize inbreds. Transgenic events produced by this method are free of morphogenic and marker genes.